Afrontamiento al estrés y modelo psicobiológico de la personalidad en estudiantes universitarios (2009)
The purpose of this study was to observe the relationship between personality dimensions suggested for Temperament/Character Model and Coping in 150 undergraduate students in a randomized stratified sample. Results indicate that participants tended to use active strategies for coping. Assumptions about biological and cultural aspects of the Personality Model are confirmed and there is evidence that coping is closely related to personality traits, especially to Character dimensions (Self directiveness and Self transcendence), and to Temperament dimensions especially to avoidance. The implications of these results are discussed.